Method for testing interlayer bonding strength of ceramic shell

By controlling the temperature change of wax material, the bonding strength between ceramic shells is tested by using thermal expansion stress, the problem of difficult to evaluate the bonding strength between ceramic shells is solved, and the rapid and accurate detection of bonding strength between ceramic shells is achieved, which is suitable for different batch testing under conditions.

CN119470251APending Publication Date: 2025-02-18SHENYANG LIMING AERO-ENGINE GROUP CORPORATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411622713.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The bonding strength between ceramic shells is difficult to be intuitively evaluated. The existing detection methods are not suitable for ceramic shells. The bonding strength between layers is closely related to the preparation process, which makes it difficult to detect and not easy to batch.

Method used

By controlling the temperature change of the wax material, the thermal expansion stress is used to test the bonding strength between the ceramic shells, and the deformation sensing and control of the expanded material are combined to achieve the testing of the bonding strength between the layers.

Benefits of technology

The interlayer bonding strength detection in various situations such as room temperature, high temperature, wetting and other conditions of different layers of ceramic shells is realized, and the weak links of the shells are quickly judged, the accuracy of data results is improved, and batch testing can be achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119470251A_ABST
    Figure CN119470251A_ABST
Patent Text Reader

Abstract

The invention relates to a method for testing interlayer bonding strength of a ceramic shell. The method comprises the following steps: step 1, testing interlayer high-temperature bonding strength of a first layer and a second layer of the shell; 2, testing the interlayer normal temperature or wetting bonding strength of the first layer and the second layer of the shell; 3, testing the high-temperature bonding strength of other layers of the shell; 4, testing the interlayer normal-temperature / wetting bonding strength of other layers of ceramic shells; according to the invention, through the combination of the structural design of the shell and the deformation sensing measurement and control of the expansion material, the interlayer bonding strength test of different layers and even different shapes of the ceramic shell under various conditions of normal temperature, high temperature, wetting and the like can be realized; the test method is simple in preparation, does not change the original preparation process of the shell, is clean and pollution-free, and can realize batch test.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of investment casting, and in particular to a method for testing the bonding strength between ceramic shell layers. Background Art

[0002] The precision casting ceramic shell is made of refractory materials and the binder is generally silica sol and other materials prepared layer by layer. The bonding strength of the ceramic shell is affected by many factors: (1) The composition, particle size distribution, specific surface area, etc. of the shell refractory material will affect the drying speed and interlayer strength of the shell. For example, the stability of the binder solution in the material, the type and amount of solvent added, the surface tension and vapor pressure will affect the volatilization, diffusion rate and capillary action of the solvent. (2) The powder-liquid ratio, viscosity, wettability and slurry hanging method of the slurry will affect the thickness, drying speed and bonding strength of the slurry layer. (3) The particle size and sanding method of the sanding material will affect the embedding degree of the sand particles, the bonding method between the two layers of the shell, and thus affect the bonding strength. (4) The thermal expansion coefficient of the wax mold is greater than that of the ceramic shell. During the dewaxing process of investment casting, this difference may cause cracks in the ceramic shell and significantly deteriorate the bonding strength.

[0003] Affected by many factors such as the properties of the mold shell material, the preparation process, the difference in thermal expansion coefficient between the wax pattern and the mold shell, the interlayer bonding strength of the mold shell often fluctuates, affecting the quality stability of the mold shell.

[0004] At present, the strength test of casting ceramic shell adopts the following methods:

[0005] (1) Compression strength test: Place the ceramic shell in a pressure testing machine and apply gradually increasing pressure until the shell is destroyed. The compression strength of the ceramic shell is evaluated by recording the maximum load-bearing capacity before destruction.

[0006] (2) Bending strength test: The ceramic shell is placed on a bending tester and a bending load is applied. The bending strength of the ceramic shell is evaluated by observing the deformation and damage of the shell.

[0007] (3) Tensile strength test: The ceramic shell is made into a tensile specimen and placed on a tensile testing machine. The tensile load is applied and the maximum tensile force and elongation before failure are recorded to evaluate the tensile strength of the ceramic shell.

[0008] (4) Impact strength test: The ceramic shell is impacted by an impact testing machine, and the impact strength of the ceramic shell is evaluated by observing the impact energy at which the shell breaks.

[0009] (5) Fatigue strength test: The ceramic shell is repeatedly loaded and unloaded to observe its deformation and damage under cyclic load to evaluate the fatigue strength of the ceramic shell.

[0010] The above methods can reflect the strength information of the ceramic shell to a certain extent, but this information belongs to the overall strength information of the shell, and it is difficult to directly reflect the bonding information between layers, which is not conducive to optimizing the bonding between layers in engineering.

[0011] Interlayer bonding strength refers to the bonding strength between layers in a multilayer material. The following methods are commonly used to test and evaluate interlayer bonding strength:

[0012] (1) Shear test method: Use a shear tester to perform a shear test on multilayer materials. Fix the sample on a shear fixture, apply shear force to cause relative sliding between the layers of material, and record the maximum shear force and displacement. By calculating the shear stress and shear strain, the bonding strength between the layers can be evaluated.

[0013] (2) Tensile test method: Use a tensile tester to perform tensile tests on multilayer materials. Fix the sample on a tensile fixture, apply tensile force at a fixed tensile speed, and record the tensile force and elongation. By calculating the tensile stress and strain, the bonding strength between the layers can be evaluated.

[0014] (3) Peel test method: Use a peel tester to perform a peel test on multi-layer materials. Fix the sample on a peel fixture, apply peel force to cause peeling failure of each layer of material, and record the maximum peel force and displacement. By calculating the peel stress and peel displacement, the bonding strength between layers can be evaluated.

[0015] (4) Failure energy method: The interlayer bonding strength is evaluated by measuring the failure energy of the material during loading such as shear, tension or peeling. This can be done through impact testing or dynamic mechanical analysis.

[0016] Among the above methods, the tensile method is not applicable to ceramic structures, the peeling method is generally applied to membrane materials, the destruction energy method requires a large number of auxiliary parameters, and only the shear method can be applied to ceramic shells. The test method of shear bond strength of materials is used to evaluate the resistance of ceramic shells under shear force. The available methods include:

[0017] (1) Shear test machine method: Use a shear test machine to perform a shear test on the ceramic shell. Clamp the shell on the test machine, apply shear force, and record the maximum shear force before the shell is damaged. The shear strength of the ceramic shell is evaluated by calculating the shear stress and shear strain of the shell.

[0018] (2) Double shear test method: The ceramic shell is made into a double shear specimen and a double shear test machine is used for shear test. Two shear clamps clamp the two sides of the specimen and apply shear force to cause shear failure. The shear strength of the ceramic shell is evaluated by recording the maximum shear force and the shear displacement of the specimen.

[0019] (3) Shear box method: The ceramic shell is placed in a shear box and a shear force is applied for testing. The design of the shear box allows the shell to be destroyed when subjected to shear force. The shear strength of the ceramic shell is evaluated by recording the destructive force and shear displacement of the shell.

[0020] (4) Oblique shear test method: At a certain oblique angle, tensile and shear forces are applied to subject the ceramic shell to a composite stress state. The shear strength of the ceramic shell is evaluated by observing the failure morphology of the shell and recording related parameters.

[0021] However, the strength of the ceramic shell itself is often unable to withstand mechanical loading, resulting in damage to the loading position rather than shear surface damage. The use of gluing to increase local strength often causes excessive penetration and affects the actual strength value. Therefore, the shear method often requires the preparation of special samples to be implemented, which is difficult to experiment and not easy to mass produce.

[0022] In addition, the shell is prepared on the wax model, the slurry coating and sanding process has a certain degree of randomness, the thickness of the sample varies, and the interlayer bonding surface is a rough surface covered with sanding particles, which makes it very difficult to locate the interlayer bonding surface of the shell. The interlayer bonding strength of the shell is closely related to the preparation process. Only the shell prepared under actual process conditions can characterize the interlayer bonding of the shell, which increases the difficulty of measuring the bonding strength.

[0023] Therefore, we can summarize the current problems in the ceramic shell interlayer bonding strength test:

[0024] (1) The preparation process of the ceramic shell is complicated, there are many factors affecting the interlayer bonding, and the interlayer bonding strength of the shell is difficult to intuitively evaluate;

[0025] (2) Commonly used methods for testing bonding strength, such as the scratch method, adhesive method, and pull-off method, are not suitable for testing between ceramic shell layers, which have low strength at room temperature, and cannot be used to test non-planar shells;

[0026] (3) The interlayer bonding strength of the shell is closely related to the preparation process. Only the shell prepared under the actual process conditions can characterize the interlayer bonding of the shell. The preparation of samples for interlayer bonding evaluation cannot change the bonding of the original shell.

[0027] (4) The evaluation of the bonding strength between shell layers often requires the comparison of multiple process conditions, and a fast and accurate evaluation method is urgently needed;

[0028] (5) During the bonding strength characterization process, excessive local stress should not be applied to cause local failure of the shell, so as not to affect the accuracy of the data. Summary of the invention

[0029] In order to solve the above technical problems, the present invention provides a method for testing the bonding strength between ceramic shell layers; the specific technical scheme is as follows:

[0030] A method for testing the bonding strength between ceramic shell layers. Thermal expansion stress is the stress caused by the change in size of an object due to temperature change. When an object is subjected to temperature changes, different parts of the object change in length or volume due to different thermal expansion coefficients, thereby generating stress inside the object. Thermal expansion stress can be calculated using the following formula:

[0031] σ=αΔT E

[0032] Among them, σ represents thermal expansion stress, α represents the linear expansion coefficient of the material, ΔT represents temperature change, and E represents the elastic modulus of the material;

[0033] By controlling the temperature change of the wax material, the thermal expansion stress of the wax can be directly determined, and then the applied force for a determined size mold shell can be obtained. By combining the mold shell structure design with the deformation sensing and control of the expansion material, the bonding strength between the mold shell layers can be tested.

[0034] The method for testing the bonding strength between ceramic shell layers comprises the following steps:

[0035] Step 1: Test the high temperature bonding strength between the first and second layers of the shell:

[0036] (1) Preparing a surface shell on the surface of a circular flat wax mold and measuring its thickness after the shell is dried;

[0037] (2) dropping a cylindrical wax material with a thickness ≈ the shell and a diameter 0.7-0.8 of the wax pattern diameter into the center of the prepared shell;

[0038] (3) If you need to test the high-temperature bonding strength of the shell, drop a rectangular wax material with a width of 0.3-0.5 cm on one side of the cylinder as a dewaxing port;

[0039] (4) preparing a second layer of mold shell on the surface of the first layer of mold shell and the wax material;

[0040] (5) Place a resistance wire on the surface of the second shell and seal it with slurry;

[0041] (6) Pass high voltage on the resistance wire to achieve flash burning of the ceramic;

[0042] (7) Add wax to the original wax position and seal with high-strength glue;

[0043] (8) placing the mold shell in the middle of a circular double-layer heating plate to increase the temperature;

[0044] (9) Observe in real time whether the shell is cracked;

[0045] (10) Calculate the shell bonding strength based on the expansion stress and bonding area;

[0046] Step 2: Test the interlayer bonding strength of the first and second layers of the shell at room temperature or wetted:

[0047] (1) Preparing a surface shell on the surface of a circular flat wax mold and measuring its thickness after the shell is dried;

[0048] (2) Drop a cylindrical wax material with a thickness of ≈ the first layer of shell and a diameter of 0.7-0.8 of the diameter of the wax mold into the center of the first layer of shell;

[0049] (3) Determine the test temperature and wet bonding strength;

[0050] (4) preparing a second layer of mold shell on the surface of the first layer of mold shell and the wax material;

[0051] (5) preparing a sealing slurry layer on the surface of the second shell;

[0052] (6) If the wet bonding strength test is required, wet the shell to the required moisture content;

[0053] (7) placing the mold shell in the middle of a circular double-layer heating plate to increase the temperature;

[0054] (8) Observe in real time whether the shell is cracked;

[0055] (9) Calculate the shell bonding strength based on the expansion stress and bonding area;

[0056] Step 3: Test the high temperature bonding strength of other layers of the shell:

[0057] (1) Determine that the bonding strength of the i-th layer of the mold shell needs to be measured;

[0058] (2) Determine the particle size of the i-1th layer of shell sand;

[0059] (3) Pour wax material with a thickness not less than 1 / 2 of the sand particle size into a circular mold with a diameter of 1 cm;

[0060] (4) keeping the wax material warm so that its viscosity is close to the viscosity of the i-1th layer of slurry;

[0061] (5) Sanding the wax material using the i-1th layer of sand;

[0062] (6) The wax and sand layer is cooled to room temperature;

[0063] (7) preparing the i-th layer of shell on the sand layer;

[0064] (8) dropping a cylindrical wax material with a thickness ≈ the i-th shell and a diameter of 0.7-0.8 of the diameter of the wax mold into the center of the i-th shell;

[0065] (9) Determine the type of test strength and test the high temperature bonding strength;

[0066] (10) dripping a rectangular wax material with a width of 0.3-0.5 cm on one side of the cylinder as a dewaxing port;

[0067] (11) preparing the (i+1) layer of shell on the surface of the (i) layer of shell and the wax material;

[0068] (12) placing a resistance wire on the surface of the i+1 layer shell and sealing it with slurry;

[0069] (13) Passing high voltage on the resistance wire to achieve flash burning of the ceramic;

[0070] (14) Add wax to the original wax position and seal with high-strength glue;

[0071] (15) placing the mold shell in the middle of a circular double-layer heating plate to increase the temperature;

[0072] (16) Observe the shell in real time to see if it is cracked;

[0073] (17) Calculate the shell bonding strength based on the expansion stress and bonding area.

[0074] Step 4: Test the room temperature / wetting bonding strength between other ceramic shell layers:

[0075] (1) Determine that the bonding strength of the i-th layer of the mold shell needs to be measured;

[0076] (2) Determine the particle size of the i-1th layer of shell sand;

[0077] (3) Pour wax material with a thickness not less than 1 / 2 of the sand particle size into a circular mold with a diameter of 1 cm;

[0078] (4) keeping the wax material warm so that its viscosity is close to the viscosity of the i-1th layer of slurry;

[0079] (5) Sanding the wax material using the i-1th layer of sand;

[0080] (6) The wax and sand layer is cooled to room temperature;

[0081] (7) preparing the i-th layer of shell on the sand layer and proceeding to step 9;

[0082] (8) dropping a cylindrical wax material having a thickness ≈ the i-th shell and a diameter 0.7-0.8 of the diameter of the wax mold into the center of the i-th shell;

[0083] (9) Determine the test strength at room temperature and wet bonding;

[0084] (10) preparing the (i+1) layer of shell on the surface of the (i) layer of shell and the wax material;

[0085] (11) preparing a sealing slurry layer on the surface of the (i+1) layer shell;

[0086] (12) If the wet bonding strength test is required, wet the shell to the required moisture content;

[0087] (13) placing the mold shell in the middle of a circular double-layer heating plate to increase the temperature;

[0088] (14) Observe the mold shell in real time to see if it is cracked;

[0089] (15) Calculate the shell bonding strength based on the expansion stress and bonding area.

[0090] Compared with the prior art, the present invention has the following beneficial technical effects:

[0091] (1) The present invention can realize the interlayer bonding strength detection of different layers and even different shapes of ceramic shells under various conditions such as room temperature, high temperature, and wet conditions;

[0092] (2) The interlayer bonding strength can be measured by deformation caused by expansion materials such as wax materials, whose expansion coefficient is insensitive to pressure and has a linear relationship with temperature. There is no gap with the shell material and no local stress concentration. The weak links of the shell can be quickly identified, and the accuracy of the data results is improved.

[0093] (3) Adopt the latest high-pressure rapid flash-firing ceramic material technology to shorten the shell preparation cycle and improve detection efficiency;

[0094] (4) By extracting the morphology of the front shell, the real morphology of the shell to be tested is fully reproduced, reducing the impact of separate preparation on the test results;

[0095] (5) The preparation is simple, does not change the original preparation process of the shell, is clean and pollution-free, and can be used for batch testing. BRIEF DESCRIPTION OF THE DRAWINGS

[0096] Figure 1 Flow chart for determining test methods for ceramic shell interlayer bonding;

[0097] Figure 2 Schematic diagram of the test method for determining the bonding between ceramic shell layers. DETAILED DESCRIPTION

[0098] A test method for the bonding strength between ceramic shell layers is designed to quantitatively evaluate the bonding between ceramic shell layers. It has the characteristics of simple preparation process, short process cycle, and the ability to achieve batch characterization, providing a new solution for the high-quality manufacturing and improvement of ceramic shells. Figure 1-2 The present invention is described in further detail.

[0099] A method for testing the bonding strength between ceramic shell layers comprises the following steps:

[0100] (1) Determine that the bonding strength between the first and second layers of the mold shell surface needs to be measured;

[0101] (2) Prepare the surface shell to be tested on the surface of a circular plane wax mold with a diameter of 1 cm. After the shell is dried, its thickness is measured to be 0.25 mm;

[0102] (3) Drop a cylindrical wax material with a thickness of ≈0.25 mm and a diameter of 0.8 cm into the center of the surface shell;

[0103] (4) Determine the room temperature bonding strength of the mold shell;

[0104] (5) preparing a second layer of shell on the surface of the surface shell and the wax material;

[0105] (6) preparing a sealing slurry layer on the surface of the second shell;

[0106] (7) Place the shell in the middle of a circular double-layer heating plate and heat it up at a rate of 10°C / min;

[0107] (8) Observe in real time whether the shell is cracked;

[0108] (9) The temperature at which the shell cracks were observed was 55°C, and the expansion stress of the wax was calculated to be 0.36 MPa. The contact area between the wax and the shell was ≈ 0.32πcm 2 The bonding area between the mold shell is 0.09πcm 2 The interlayer bonding strength between the shell surface layer and the second layer is calculated to be approximately 1.12Mpa.

Claims

1. A method for testing the bonding strength between ceramic shell layers, characterized in that: Thermal expansion stress is the stress caused by the change in size of an object due to temperature changes. When an object is subjected to temperature changes, different parts of it change length or volume due to different thermal expansion coefficients, thus generating stress inside the object. Thermal expansion stress can be calculated using the following formula: σ=αΔT E Among them, σ represents thermal expansion stress, α represents the linear expansion coefficient of the material, ΔT represents temperature change, and E represents the elastic modulus of the material; By controlling the temperature change of the wax material, the thermal expansion stress of the wax can be directly determined, and then the applied force for a determined size mold shell can be obtained. By combining the mold shell structure design with the deformation sensing and control of the expansion material, the bonding strength between the mold shell layers can be tested.

2. A method for testing the bonding strength between ceramic shell layers according to claim 1, characterized in that: The steps include: Step 1: Test the high temperature bonding strength between the first and second layers of the shell (1) Preparing a surface shell on the surface of a circular flat wax mold and measuring its thickness after the shell is dried; (2) dropping a cylindrical wax material with a thickness ≈ the shell and a diameter 0.7-0.8 of the wax pattern diameter into the center of the prepared shell; (3) If you need to test the high-temperature bonding strength of the shell, drop a rectangular wax material with a width of 0.3-0.5 cm on one side of the cylinder as a dewaxing port; (4) preparing a second layer of mold shell on the surface of the first layer of mold shell and the wax material; (5) Place a resistance wire on the surface of the second shell and seal it with slurry; (6) Pass high voltage on the resistance wire to achieve flash burning of the ceramic; (7) Add wax to the original wax position and seal with high-strength glue; (8) placing the mold shell in the middle of a circular double-layer heating plate to increase the temperature; (9) Observe in real time whether the shell is cracked; (10) Calculate the shell bonding strength based on the expansion stress and bonding area; Step 2: Test the interlayer bonding strength of the first and second layers of the shell at room temperature or wetted (1) Preparing a surface shell on the surface of a circular flat wax mold and measuring its thickness after the shell is dried; (2) Drop a cylindrical wax material with a thickness of ≈ the first layer of shell and a diameter of 0.7-0.8 of the diameter of the wax mold into the center of the first layer of shell; (3) Determine the test temperature and wet bonding strength; (4) preparing a second layer of mold shell on the surface of the first layer of mold shell and the wax material; (5) preparing a sealing slurry layer on the surface of the second shell; (6) If the wet bonding strength test is required, wet the shell to the required moisture content; (7) placing the mold shell in the middle of a circular double-layer heating plate to increase the temperature; (8) Observe in real time whether the shell is cracked; (9) Calculate the shell bonding strength based on the expansion stress and bonding area; Step 3: Test the high temperature bonding strength of other layers of the shell (1) Determine that the bonding strength of the i-th layer of the mold shell needs to be measured; (2) Determine the particle size of the i-1th layer of shell sand; (3) Pour wax material with a thickness not less than 1 / 2 of the sand particle size into a circular mold with a diameter of 1 cm; (4) keeping the wax material warm so that its viscosity is close to the viscosity of the i-1th layer of slurry; (5) Sanding the wax material using the i-1th layer of sand; (6) The wax and sand layer are cooled to room temperature; (7) preparing the i-th layer of shell on the sand layer; (8) dropping a cylindrical wax material with a thickness ≈ the i-th shell and a diameter of 0.7-0.8 of the diameter of the wax mold into the center of the i-th shell; (9) Determine the type of test strength and test the high temperature bonding strength; (10) dripping a rectangular wax material with a width of 0.3-0.5 cm on one side of the cylinder as a dewaxing port; (11) preparing the (i+1) layer of shell on the surface of the (i) layer of shell and the wax material; (12) placing a resistance wire on the surface of the i+1 layer shell and sealing it with slurry; (13) Passing high voltage on the resistance wire to achieve flash burning of the ceramic; (14) Add wax to the original wax position and seal with high-strength glue; (15) placing the mold shell in the middle of a circular double-layer heating plate to increase the temperature; (16) Observe the shell in real time to see if it is cracked; (17) Calculate the shell bonding strength based on the expansion stress and bonding area. Step 4: Test the room temperature / wetting bonding strength between other ceramic shell layers (1) Determine that the bonding strength of the i-th layer of the mold shell needs to be measured; (2) Determine the particle size of the i-1th layer of shell sand; (3) Pour wax material with a thickness not less than 1 / 2 of the sand particle size into a circular mold with a diameter of 1 cm; (4) keeping the wax material warm so that its viscosity is close to the viscosity of the i-1th layer of slurry; (5) Sanding the wax material using the i-1th layer of sand; (6) The wax and sand layer are cooled to room temperature; (7) preparing the i-th layer of shell on the sand layer, and proceeding to step 9; (8) dropping a cylindrical wax material with a thickness ≈ the i-th shell and a diameter of 0.7-0.8 of the diameter of the wax mold into the center of the i-th shell; (9) Determine the test strength at room temperature and wet bonding; (10) preparing the (i+1) layer of shell on the surface of the (i) layer of shell and the wax material; (11) preparing a sealing slurry layer on the surface of the (i+1) layer shell; (12) If the wet bonding strength test is required, wet the shell to the required moisture content; (13) placing the mold shell in the middle of a circular double-layer heating plate to increase the temperature; (14) Observe the mold shell in real time to see if it is cracked; (15) Calculate the shell bonding strength based on the expansion stress and bonding area.